Father–Child Communication in Migrant Families and Adult Attachment Among Young Pakistani Adults (International Journal of Politics & Social Sciences Review (IJPSSR), 2026)
Father–child communication constitutes a critical relational mechanism through which attachment orientations are shaped across development. In migrant families, prolonged paternal absence may disrupt everyday emotional exchanges, with enduring implications for attachment security during emerging adulthood. Drawing on attachment theory and family systems perspectives, the present study examined the association between father–child communication and adult attachment orientations among young Pakistani adults raised in migrant family contexts, and tested family functioning as a mediating mechanism. Using a cross-sectional correlational design, data were collected from 600 Pakistani young adults aged 18–23 years who reported a history of paternal labor migration during childhood. Participants completed Urdu-validated measures of father–child communication, adult attachment anxiety and avoidance, and family functioning. Results indicated that higher perceived quality of father–child communication was significantly associated with lower attachment anxiety and avoidance and greater attachment security. Mediation analyses revealed that family functioning partially mediated the relationship between father–child communication and adult attachment security. These findings advance attachment and family systems theory by demonstrating culturally specific relational pathways through which paternal communication shapes adult attachment security in migration-affected families. The study underscores the importance of culturally responsive family interventions and paternal engagement practices in migration-affected contexts.
Keywords: Father–Child Communication, Adult Attachment, Migrant Families, Emerging Adulthood, Pakistan, Family Functioning